High thermoelectric performance of rapidly microwave-synthesized Sn1−δS. Issue 4 (29th June 2020) - Prado-Gonjal, Jesús; Gainza, Javier; Aguayo, Isabel; Durá, Óscar Juan; Rodríguez-Pérez, Sara; Serrano-Sánchez, Federico; Nemes, Norbert M.; Fernández-Díaz, María Teresa; Alonso, José Antonio; Morán, Emilio
Abstract : Promising thermoelectric properties were found for polycrystalline Sn1 −δ S synthesized by a microwave-hydrothermal route ( ZT = 0.76 at 523 K). Abstract : Phase-pure polycrystalline Sn1 −δ S has been prepared using a one-step microwave-hydrothermal procedure. Its structural characterization by neutron powder diffraction and transmission electron microscopy shows an orthorhombic Pnma phase at room temperature with the presence of a significant amount of Sn vacancies (Sn0.87 S), randomly located in the crystal structure. This work proves that this inexpensive 2D material, constituted by high abundance elements, is a promising candidate for thermoelectric applications. This is confirmed by its relatively high carrier density and good mobility (2.5 × 10 18 cm −3 and 13 cm 2 V −1 s −1 at room temperature, respectively) found in the microwave-hydrothermal-synthesized sample, which favours high thermoelectric performance. In addition, a remarkably high Seebeck coefficient (682 μV K −1 ) combined with low electrical resistivity (5.6 × 10 −4 Ω m) and thermal conductivity (0.57 W m −1 K −1 ) at 523 K produces a reasonably high figure of merit ZT of 0.76.